Pemberhentian Anggota Dewan Perwakilan Rakyat Dalam Peraturan Perundang-Undangan Di Indonesia - Arif Mohamad Azhar Annas; Dwi Putri Cahyawati; Nur Rohim Yunus (STAATSRECHT: Indonesian Constitutional Law Journal, 2018)
Abstract.Problems in dismissing board members by their supporting political parties are still a polemic in the constitutional system of the Republic of Indonesia. The presumption of council members as an extension of the party is still a heated debate. So that a council member who should be a representative of the people seems to be a party representative. The regulation of dismissal of members of political parties is contained in article 16 of Act No. 2 of 2011 concerning Political Parties which explains that dismissal of party members is based on several factors, such as death, resignation in writing, becoming a member of another political party and violating code of ethics for Political Parties. This discussion uses qualitative research methods with a literature review approach.Keywords: Dismissal, Board Members, Political Parties Abstrak.Problematika pemberhentikan anggota dewan oleh partai politik pengusungnya masih menjadi polemik dalam sistem ketatanegaraan Republik Indonesia. Adanya anggapan anggota dewan sebagai kepanjangan tangan partai, masih menjadi perdebatan yang sengit. Sehingga seorang anggota dewan yang seharusnya menjadi wakil rakyat seolah menjadi wakil partai. Akan halnya pengaturan pemberhentian terhadap anggota partai politik tertuang dalam pasal 16 Undang-Undang Nomor 2 tahun 2011 tentang Partai Politik yang menjelaskan bahwa pemberhentian terhadap anggota partai didasari oleh beberapa faktor, seperti meninggal dunia, mengundurkan diri secara tertulis, menjadi anggota partai politik lain dan melanggar kode etik Partai Politik. Pembahasan ini menggunakan metode penelitian kualitatif dengan pendekatan literatur review.Kata Kunci: Pemberhentian, Anggota Dewan, Partai Politik